Assessing the risk of venous thromboembolic events in women taking progestin-only contraception: a meta-analysis. (7th August 2012) - Mantha, S; Karp, R; Raghavan, V; Terrin, N; Bauer, K A; Zwicker, J I
Abstract : Objectives To evaluate the risk of venous thromboembolic events associated with the use of progestin-only contraception and whether that risk differs with the mode of drug delivery (oral, intrauterine, or depot injection). Design Systematic review and meta-analysis of randomised controlled trials and observational studies. Data sources Pubmed, Embase, Cochrane Library, and reference lists of relevant reviews. Study selection Randomised controlled trials and case-control, cohort, and cross sectional studies with venous thromboembolic outcome for progestin-only contraception reported relative to a non-hormone comparator group. Data extraction Data were extracted by two independent investigators, and consensus for inclusion was reached after assessment by additional investigators. Results Among the 2022 unique references identified by all searches, eight observational studies fulfilled inclusion criteria. A total of 147 women across all studies were diagnosed with a venous thromboembolic event while taking progestin-only contraception, and the summary measure for the adjusted relative risk of a venous thromboembolic episode for users versus non-users of a progestin-only contraceptive was, based on the random effects model, 1.03 (95% CI 0.76 to 1.39). Subgroup analysis confirmed there was no association between venous thromboembolic risk and progestin-only pills (relative risk 0.90 (0.57 to 1.45)) or a progestin intrauterine device (0.61 (0.24 to 1.53)). The relative risk of a venous thromboembolic event for users of an injectable progestin versus non-users was 2.67 (1.29 to 5.53). Conclusions Published data assessing the risk of venous thromboembolism in women prescribed progestin-only contraception are limited. In this meta-analysis of eight observational studies, the use of progestin-only contraception was not associated with an increased risk of venous thromboembolism compared with non-users of hormonal contraception. The potential association between injectable progestins and thrombosis requires further study.